2018
DOI: 10.1371/journal.pone.0191151
|View full text |Cite
|
Sign up to set email alerts
|

Rural versus urban academic hospital mortality following stroke in Canada

Abstract: IntroductionStroke is one of the leading causes of death in Canada. While stroke care has improved dramatically over the last decade, outcomes following stroke among patients treated in rural hospitals have not yet been reported in Canada.ObjectivesTo describe variation in 30-day post-stroke in-hospital mortality rates between rural and urban academic hospitals in Canada. We also examined 24/7 in-hospital access to CT scanners and selected services in rural hospitals.Materials and methodsWe included Canadian I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
3
24
1
1
Order By: Relevance
“…Over 2.4 million Veterans seek care from Veterans Health Administration (VHA) emergency departments (EDs) each year, and 40% of these Veterans live in rural America [1]. Providing high quality emergency care in low-volume centers is challenging, and several prior studies have suggested that clinical outcomes are worse in low-volume rural hospitals [2][3][4][5][6][7][8][9]. These volumeoutcome relationships could be attributable to provider training and experience, staffing, or resource allocation in low-volume facilities [10].…”
Section: Introductionmentioning
confidence: 99%
“…Over 2.4 million Veterans seek care from Veterans Health Administration (VHA) emergency departments (EDs) each year, and 40% of these Veterans live in rural America [1]. Providing high quality emergency care in low-volume centers is challenging, and several prior studies have suggested that clinical outcomes are worse in low-volume rural hospitals [2][3][4][5][6][7][8][9]. These volumeoutcome relationships could be attributable to provider training and experience, staffing, or resource allocation in low-volume facilities [10].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Interventions such as thrombolysis, endovascular thrombectomy (EVT), stroke unit care, and rehabilitation are associated with improved outcomes after stroke, but require resources and expertise that are not available in all centers and are less likely to be located in rural areas. 1,[4][5][6][7] Poor geographic access to medical care has been associated with lower quality of care and with worse outcomes for a variety of medical conditions. 8,9 Although organized systems of stroke care in Ontario are designed to optimize care across the continuum for an entire region, it is not known whether current stroke systems provide adequate access for residents of rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…(22) This finding echoes previous reports that highlighted significant disparities in access to high-quality emergency care in Canadian rural communities. (23,24) In the same way it was done for trauma care across the country, Canadian decision-and policy-makers could use the ED-HSMR to trigger in-depth performance assessment to help identify opportunities for improving emergency care structures and processes to improve patient outcomes. As worrisome as they are, wait times henceforth do not appear to be the only important risk factor impacting outcomes of ED patients with emergency sensitive conditions.…”
Section: Discussionmentioning
confidence: 99%